THE INFLUENCE OF THE AUDIT COMMITTEE, THE REPUTATION OF THE PUBLIC ACCOUNTING OFFICE, FINANCIAL DISTRESS, AND COMPANY SIZE ON AUDIT DELAY: Case Study of Hotel and Tourism Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2014-2021 - Alya Afsilah; Santi Damayanti (Universitas Indonesia Membangun, 2023)
The purpose of this study is to determine the influence of the audit committee, the reputation of the public accounting firm, Financial Distress, and Company Size on audit Delay. The method used in this research is a quantitative method with a descriptive and verification approach. The data analysis technique used in this study is the classical assumption test, multicollinearity test, heteroscedasticity test, multiple linear regression, coefficient product moment Pearson and the coefficient of determination, and hypothesis testing using SPSS version 26. Based on the results of the study, it was shown that in testing the hypothesis (t-test) the results were obtained: (1) the Audit Committee did not affect audit Delay. (2) Reputation of Public Accounting Firm significant positive effect on audit Delay. (3) Financial Distress does not affect audit Delay. (4) Company size does not affect audit Delay. (5) While research on the F Test simultaneously obtained results (6) Audit Committee, Reputation of Public Accounting Firms, Financial Distress, and Company Size toAudit Delay positive and significant effect on Audit Delay.